Santa Maria dos Anjos Chapel: one alternative work - Carranza, Edite Galote (Pós. Revista do Programa de Pós-Graduação em Arquitetura e Urbanismo da FAUUSP, 2017)
Celebrating one hundred years of the birth of architect Lina Bo Bardi,her works are still relevant today, inciting the curiosity of researchers,artists, and other architects all over the world. This is due to the quality and scope of her creations in the fields of scenography, artistic design,critiques, and, of course, architecture which are particularly filled with artistic subjectivity, ideals, and a philosophical backdrop. Among her projects, the one we should pay closest attention to is the Santa Maria dos Anjos Chapel, 1978, and located in the city of Vargem Grande Paulista. Although it might be considered a simple project, it is in fact a dense and syncretic work which is an representative project of the alternative to status quo architectural. This article aims to analyze the chapel and its relation to the concept of national-popular, concept of Te-Ato, Franciscan faith and culture high culture and popular culture in order to understand its communicating directly with the extensive cultural and political scenario.